How to talk to an autistic kid - Stefanski, Daniel; Braun, Eric; Mitchell, Hazel (Minneapolis, MN : Free Spirit Pub., 2011)
A collection of personal stories, knowledgeable explanations, and supportive advice written by a fourteen-year-old autistic boy to help provide readers with the confidence and tools necessary to befriend autistic kids.
Keywords: Autistic youth; Interpersonal relations; Autism in children; Autism; Autism; People with mental disabilities; Social skills